2019
DOI: 10.1155/2019/6760121
|View full text |Cite
|
Sign up to set email alerts
|

Reward Processing under Chronic Pain from the Perspective of “Liking” and “Wanting”: A Narrative Review

Abstract: The therapeutic goals of patients with chronic pain are not only to relieve pain but also to improve the quality of life. Chronic pain negatively affects various aspects of daily life, such as by decreasing the motivation to work and reward sensitivity, which may lead to difficulties in daily life or even unemployment. Human and animal studies have shown that chronic pain damages reward processing; the exploration of associated internal mechanisms may aid the development of treatments to repair this damage. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…For the study of depressive-like behavior in the rodent, the sucrose preference test has traditionally been used in which a decrease in the preference or in the amount of sucrose solution consumed is considered anhedonic behavior . However, this type of test may not be sensitive enough, probably because it would only be measuring the consummatory component without considering the appetitive component (also known as approach or seeking behavior). In fact, the studies carried out to date using this test in pain models are contradictory, with some studies showing anhedonic behavior while others not. , Recently, our group has presented data using white chocolate as a highly palatable food in which an increase in the latency of approach and decreased consumption after visceral nociceptive stimulation were observed; making the study of this type of motivated responses feasible in chronic pain models …”
mentioning
confidence: 99%
“…For the study of depressive-like behavior in the rodent, the sucrose preference test has traditionally been used in which a decrease in the preference or in the amount of sucrose solution consumed is considered anhedonic behavior . However, this type of test may not be sensitive enough, probably because it would only be measuring the consummatory component without considering the appetitive component (also known as approach or seeking behavior). In fact, the studies carried out to date using this test in pain models are contradictory, with some studies showing anhedonic behavior while others not. , Recently, our group has presented data using white chocolate as a highly palatable food in which an increase in the latency of approach and decreased consumption after visceral nociceptive stimulation were observed; making the study of this type of motivated responses feasible in chronic pain models …”
mentioning
confidence: 99%
“…However, results between studies of acute and chronic pain might not be comparable: It is proposed that changes in the function and structure of the brain's reward network are involved in the pathophysiology of chronic pain [58,59], but not in acute pain. For example, in experimental studies inducing acute pain in humans, motivation to obtain reward was increased [25], whereas chronic pain seems to negatively impact this wanting quality [24]. The second limitation to consider is our measurement of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to assess the relationship between chronic pain and savoring of aesthetic experiences. Only few human studies have directly explored the relationship between chronic pain and any form of reward processing [24,25]. Previous studies, mainly based on animal research, found evidence for a negative relationship between chronic pain and the wanting, but not the liking quality of reward processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic studies addressing risk and protective factors associated with the development of persistent pain after torture are lacking. However, pain is inflicted in torture often under severe conditions with extreme stress that may have profound effects on neurophysiology and the processing of pain, according to previous pain theories that we described (Liu et al, 2019).…”
Section: Nociplastic Mechanisms and Altered Central Pain Modulationmentioning
confidence: 96%